Factors influencing diet barriers among outpatients with poorly‐controlled type 2 diabetes: A descriptive correlational study. (28th September 2018) - Cheng, Ling Jie; Wu, Vivien Xi; Dawkes, Susan; Lim, Suan Tee; Wang, Wenru
Abstract: The aim of the present descriptive correlational study was to investigate diet barriers and their influencing factors among outpatients with poorly‐controlled type 2 diabetes in Singapore. One hundred and ten patients with poorly‐controlled type 2 diabetes were recruited from a tertiary hospital in Singapore. The Personal Diabetes Questionnaire and Appraisal of Diabetes Scale were used to measure the study variables. Our participants reported that the most common diet barriers were eating out, followed by food cravings. Eating problems and negative diabetes appraisal were identified as significant predictors of diet barriers. The findings laid the groundwork with preliminary findings for the development of culturally‐tailored and patient‐centered education programs to enhance eating behaviors and promote positive appraisal.